SMT19969 for Clostridium difficile infection (CDI): in vivo efficacy compared with fidaxomicin and vancomycin in the hamster model of CDI. (3rd February 2015) - Sattar, Abdul; Thommes, Pia; Payne, Lloyd; Warn, Peter; Vickers, Richard J.
Abstract: Objectives: SMT19969 is a novel narrow-spectrum antimicrobial under development for the treatment of Clostridium difficile infection (CDI). The objectives were to assess the relative efficacies of SMT19969, vancomycin and fidaxomicin in the hamster model of CDI. Methods: Hamsters were infected with either C. difficile BI1 (ribotype 027) or C. difficile 630 (ribotype 012) prior to treatment with vehicle, SMT19969, fidaxomicin or vancomycin for 5 days. Animals were further monitored through to day 28 and survival recorded. Plasma and gastrointestinal concentrations of SMT19969 following single and repeat administration in infected hamsters were determined. Results: Following infection with C. difficile BI1, treatment with SMT19969, vancomycin and fidaxomicin resulted in 100% survival during the 5 day dosing period, with 90%–100% of animals receiving SMT19969 and fidaxomicin surviving during the post-dosing follow-up period. Whilst protective during treatment, onset of mortality was observed on day 11 in animals treated with vancomycin, with a 10% survival recorded by day 28. Similar results were observed for SMT19969 and vancomycin following infection with C. difficile 630, with day 28 survival rates of 80%–100% and 0%, respectively. Fidaxomicin protected animals infected with C. difficile 630 from mortality during dosing, although day 28 survival rates varied from 0% to 40% depending on dose. Plasma levels of SMT19969 were typically below the limit of quantification, but levels in the gastrointestinal tract remained far in excess of the MIC. Conclusions: These data show that SMT19969 is highly effective at treating both acute infection and preventing recurrent disease and support continued investigation of SMT19969 as a potential therapy for CDI.